Review: Danielle Bazzi, Heidi Schär Sall, David Signer, Elena Wetli & Dieter Wirth (2000). Fluchten, Zusammenbrüche, Asyl. Fallstudien aus dem Ethnologisch-Psychologischen Zentrum in Zürich [Escapes, Breakdowns, Asylum. Case Studies from the Ethnographic-Psychological Center in Zurich] - Victoria Hegner (Forum: Qualitative Social Research, 2001)
URN: urn:nbn:de:0114-fqs0102345